Prostate cancer awareness among transgender women after gender‐affirming surgery. Issue 10 (13th April 2022) - Pitak‐Arnnop, Poramate; Messer‐Peti, Robert; Tangmanee, Chatpong; Neff, Andreas; Meningaud, Jean‐Paul
Abstract: Background: The prostate gland remains unresected during gender‐affirming surgery (GAS) for transgender women (TGW), and may develop malignancies in later life. We sought to evaluate prostate cancer awareness (PCA) among post‐GAS TGW. Methods: The investigators implemented a cross‐sectional study and enrolled a sample of Thai post‐GAS TGW without medical background. Predictor variables were categorized as demographic, clinical, operative, or postoperative. The outcome variable was PCA (yes/no). Appropriate statistics were computed, and a p ‐value ≤ 0.05 was considered statistically significant. Results: The sample consisted of 100 Thai post‐GAS TGW (4% bisexual, 12% bachelor [or higher] graduates, 51% service workers, 64% had monthly net income <40, 000 TB [or ca. 1050 Euro], 92% operated by plastic surgeons) with a mean age of 26.2 ± 5.4 years (range: 18–45). On bivariate analysis, PCA was significantly associated with educational level ( p  = 0.007; adjusted odd ratio [ORadj. ]: 5.85; 95% confidence interval [95% CI]: 1.65–20.69), being operated ≥ 10 years  ( p  = 0.01; ORadj. : 0.16; 95% CI: 0.04–0.76), self‐recognition of the remaining prostate gland ( p  = 0.0001; ORadj. : 0.02; 95% CI: 0–0.12), and emphasis on PCA by the GAS operator ( p  = 0.01; ORadj. : 0.07; 95% CI: 0.01–0.63). Multiple linear regression analysis revealed a statistically significant, positive correlation ( r  = 0.78; p  = 0.0001) among these four predictors, and continued to confirm the positive effect on PCA in TGW with high education and realization of the prostate gland ( r  = 0.56; p  = 0.04) or information on PCA by the operator ( r  = 0.68; p  = 0.003). Conclusion: The GSA operator should intensively inform TGW about the remnant prostate and the risk of PC, especially those with low and middle levels of education attained.